Knowledge Sharing-Based HR Capability Development to Achieve Sustainable Development Goals - Raniasari Bimanti Esthi; Indra Setiawan; Norbertus Citra Irawan (DEAL: International Journal of Economics and Business, 2023)
This research reveals the challenges human resource (HR) capabilities face in achieving Sustainable Development Goals (SDGs) in Indonesia. In particular, the issues of inadequate skills, employment opportunities, and investment are highlighted. This research focuses on the relationship between Human Resource Capability (HRC), Green Knowledge Sharing (GKS), and the achievement of SDGs goals 8 (Decent Work and Economic Growth) and 9 (Industry, Innovation and Infrastructure). By adopting a case study method involving respondents from all over Indonesia, this research found that increasing HRC can encourage GKS, which supports the achievement of the two SDGs goals. This research suggests providing education and training that focuses more on environmental and sustainability issues to improve HR qualifications. In addition, the policy implies the importance of investing in improving human resource capabilities and promoting green knowledge-sharing practices. This research provides in-depth insight into how these factors are interrelated and contribute to global efforts to achieve sustainable development, with potential practical implications for designing more effective HR policies and management to support the SDGs in the future.